1979
DOI: 10.1088/0029-5515/19/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of electron-cyclotron-resonance-heated tokamak power reactors

Abstract: A set of constraints is derived for the operating characteristics of tokamak power reactors which are bulk heated by electron cyclotron resonance heating (ECRH).Four heating modes are considered: ordinary wave heating at the electron cyclotron frequency, 0, and at the second harmonic frequency, 20, and extraordinary wave heating at 0 and at 20. For ordinary wave heating at 1, which appears to be the most promising method, the wave frequency w z 0 must exceed the plasma frequency, W p, for wave penetration into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The auxiliary power required for steady state operation can also provide the external power needed to reach ignition temperatures in fusion plasmas. Early reactor designs considered, for example, neutral beam and electron cyclotron resonance RF heating (ECRH) technologies [28]. On the basis of such studies, important directions were identified for technology development.…”
Section: Mfe Reactor Technology and Designmentioning
confidence: 99%
“…The auxiliary power required for steady state operation can also provide the external power needed to reach ignition temperatures in fusion plasmas. Early reactor designs considered, for example, neutral beam and electron cyclotron resonance RF heating (ECRH) technologies [28]. On the basis of such studies, important directions were identified for technology development.…”
Section: Mfe Reactor Technology and Designmentioning
confidence: 99%